Teachers’ Perceptions of the Impact of Continuing Professional Development on Their Professional Practice in a Further Education College in the West Midlands - Lisa Bartleton (Educational Futures)
This paper explores stakeholders’ views on the impact of continuing professional development on teaching practice in further education. Continuing professional development (CPD) is a broad term that describes the activities, learning and support that teachers undertake throughout their professional career. The importance of teachers’ professional development is that it should enhance the quality of teaching and learning in educational establishments (Pedder and Opfer, 2011). Michael and Watson, (2015) see the underpinning the strength of CPD in that it allows teachers as professionals to take responsibility for their own learning and development, exercising their own professional autonomy, thus enabling them to embrace change and better meet the needs of the students they teach. In this study data was collected using the qualitative methods of semi-structured interviews and questionnaires to explore perceptions of the usefulness of CPD in a further education college. The key findings show the overall benefits of CPD to teachers and learners and the impact this has on current teaching practice. This leads to the conclusion that teachers recognise and value CPD as it facilitates the updating of subject knowledge, helps share good practice, provides opportunities for collaboration and is seen to aid reflection and future progression. However, this research found that CPD did not realise the potential for raising standards of achievement due to the prescriptive nature of CPD as it is currently undertaken.